Gewalt als Risiko in der offenen Jugendarbeit Eine professionstheoretische Analyse - Unterkofler, Ursula (Verlag Barbara Budrich, 2014)
How do professionals in open youth work deal with violence among young people? On the basis of an ethnographic study based on Grounded Theory, the author points out different processing strategies. The results show that professionals primarily interpret and deal with violence as a risk. It becomes clear that the action strategies of the social workers refer to approaches of sanctioning pedagogy on the one hand and youth work as education on the other. The ethnographic study in the style of Grounded Theory with a professional theoretical perspective was conducted in five different youth clubs over a period of one and a half years. Although violence between young people is relatively rare, it is omnipresent in the thinking of professional forces as a scenario that could develop. The presentation of typical situations from youth clubs shows that they constantly act in the sense of violence prevention close to everyday life and try to prevent a violent development through targeted action strategies. Within this framework, it becomes clear that two patterns of professional problem construction are central - on the one hand, following the sanctioning pedagogy, on the other hand, an understanding of youth work as education. Against this background, the interpretation and action strategies of skilled workers were discussed.